The thermoluminescence response of Ge-doped flat fibre for proton beam measurements: a preliminary study - Hassan, M. F.; Rahman, W. N. Wan Abdul; Fadzil, M. S. Ahmad; Tominaga, T.; Geso, M.; Akasaka, H.; Bradley, D. A.; Noor, N. Mohd. (Institute of Physics Publishing, 2017)
The aim of this study was to investigate the thermoluminescence (TL) response of fabricated 2.3 mol% and 6.0 mol% germanium (Ge) doped flat optical fibres to proton irradiation. The fundamental dosimetric characteristics of the fibres have been investigated including dose linearity, reproducibility and fading. The thermoluminescent dosimeters (TLDs) were used as a reference dosimeter to allow the relative response of the fibres. The results show that Ge-doped flat fibres offer excellent dose linearity over the dose range from 1 Gy up to 10 Gy with correlation of determination (R2) of 0.99. The fibres also demonstrated good reproducibility within the standard deviation (SD) of 0.86% to 6.41%. After 96 days post-irradiation, TLD-100 chips gave rise to the least loss in TL signal at around 18% followed by fabricated 2.3 mol% Ge-doped flat fibres about 24%. This preliminary study has demonstrated that the proposed fabricated Ge-doped flat fibre offers a promising potential for use in proton beam measurements.